HUBUNGAN ANTARA KEBERSIHAN DIRI DAN PRAKTIK HIGIENE PENJUAL DENGAN KEBERADAAN Escherichia coli PADA NASI RAMES DI PASAR TRADISIONAL KOTA SEMARANG - Mutia Farida Akhsanti; Retno Hestiningsih; Martini Martini; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat, 2019)
Nasi rames is favorite food for many people in all ages, because it tastes good and easy to find. The process of making nasi rames is still traditional and lacks attention of hygiene and sanitation aspects and it can cause bacteria contamination. Escherichia coli is indicator of nasi rames's contamination. The purpose of this study was to determine ralationship between personal hygiene and hygiene practice with the existence of Escherichia coli in nasi rames sold in traditional market of Semarang City. The study design was analytic descriptive using survey method and laboratory examination with cross sectional approach. The study sample taken were 38 nasi rames using purposive sampling method from nasi rames sellers in traditional markets of Semarang City. Data was analyzed using Fisher exact test. The results showed that 30 (78,9%) nasi rames were found to be positive for Echerichia coli. Statistical results showed a relation between personal hygiene (p=0,012) and hygiene practices (p=0,017) with the existence of Escherichia coli in nasi rames. From this study, it can be concluded that personal hygiene and hygiene practices have significant relationship with the existence of Escherichia coli in nasi rames sold in traditional markets of Semarang City.